Obesity in Patient with Grown Up Congenital Heart Disease (GUCH) Ventricular Septal Defect (VSD) with Pulmonary Hypertension in Sanglah Hospital, Bali - Natasya N., et al (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Obesity in Patient with Grown Up Congenital Heart Disease (GUCH) Ventricular Septal Defect (VSD) with Pulmonary Hypertension in Sanglah Hospital, Bali